"A country with land but no habitat": Women, violent accumulation and negative-value in Yvonne Vera's The Stone Virgins. Issue 3 (4th May 2017) - Graham, James
Abstract: In the work of Zimbabwean novelist Yvonne Vera, land is shown to be a complex and contested resource to which the typically abject fates of her female protagonists are inextricably bound. As she put it in a 2001 interview shortly before the publication of her final novel, "the connection between women and land in Zimbabwe is negative". This article situates Vera's work in the context of debates over Zimbabwean land reform, and considers examples of how the "negative" connection between women and land is articulated in her fiction through contrasting leitmotifs of abjection and habitat, culminating in the cautiously redemptive conclusion of her last published novel, The Stone Virgins (2002). The discussion draws on Silvia Federici's work on women, the body and primitive accumulation and on Jason Moore's theory of negative-value in the capitalist world-ecology, to account for why, in Vera's work, the female body is invariably positioned, abjectly, at the nexus of colonial governance and what David Moore has described as Zimbabwe's postcolonial regime of "violent accumulation".